Adaptable maps for people with autism - Perez, C.; Falkmer, Marita; McMeekin, David; Tan, Tele (2018)
© 2018 Copyright held by the owner/author(s). Publication rights licensed to ACM. People with autism require adapntations on their user interfaces to be able to engage and correctly use digital technology. Based on the current literature for user interfaces for people with autism, this paper presents a web application of maps adapted to their needs. According to his preferences it is possible to change how the map looks and how the information is displayed on the screen. The development is presented in the URL: Http://www.adaptableinterface.com.